Menggali Narasi, Melestarikan Tradisi: Warisan Konsep Water Preservation Pada Makam Sunan Muria - Titis Thoriquttyas; Nurul Ahsin (UIN Sunan Kalijaga Yogyakarta, 2022)
This study examines the legacy of Sunan Muria's thoughts on conserving water sourced from the sign and symbol around the graves The existence of water plays an important role in the religious studies. Islam, Christianity, Judaism, Hinduism and Buddhism use water as an important component in every religious ritual. Therefore, one of the contemporary issues in Islamic studies that has attracted the attention of scholars is water conservation. Based on initial observations, researchers found a water jar that is sacred by the local community. Social, religious, and cultural narratives about sacred concepts are the main points of this research. In addition, based on extensive field research, various interviews and literature studies on related topics, the researcher explores the complexity of the heritage of water conservation thought in Sunan Muria's perspective through the identification of signs and symbols on their tombs from the concepts of eco-theology; bi'ah al-hudry.